Management Improves Student Activities In The Digital Era To Achieve A Pancasila Student Profile - Rusani Jaelani; Alwi Bangkis A.S; Sandy Sanjaya (CV. Ksatria Siliwangi, 2023)
This study aims to increase student activity in achieving Pancasila student profiles in the digital era. In the digital era, learning can be carried out boldly, but this requires planning and organizing the right learning. One way to increase student activity is to choose learning materials that can be integrated with the Pancasila student profile. The selection of appropriate learning materials can help students understand the values of Pancasila and apply them in everyday life. In addition, educators also need to have competence in digital learning, such as planning and organizing learning, delivering skills, and mastering learning media. In this research, it is hoped that effective ways can be found to increase student activity in achieving a Pancasila student profile in the digital era.